2007
DOI: 10.1016/j.neuropharm.2007.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Presynaptic AMPA and kainate receptors increase the size of GABAergic terminals and enhance GABA release

Abstract: SUMMARYIn the developing cerebellum, NMDA receptors promote the maturation of axonal terminals of inhibitory interneurons. We compared the effects of AMPA/kainate receptor agonists in cultured cerebellar cells from GAD65-eGFP mice. Both AMPA and kainate augmented granule cell survival without affecting interneurons. The action of kainate was blocked by an AMPA but not by a NMDA receptor antagonist, suggesting AMPA receptor involvement. AMPA and kainate increased the size of the GABAergic terminals and the acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Our Ca 2+ imaging experiments with (PN 19–21) animals confirm the hypothesis of a developmental switch (Bureau & Mulle, 1998) that could correspond to a displacement of AMPARs from the axonal to the somato‐dendritic compartment. Interestingly, it has been reported that presynaptic ionotropic glutamate receptors promote the maturation of GABAergic basket/stellate interneurones and increase the size of their axonal terminals thus enhancing GABA release (Fiszman et al 2005, 2007). It seems likely that activation of presynaptic Ca 2+ ‐permeable AMPARs represents an important step in the developing cerebellum.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our Ca 2+ imaging experiments with (PN 19–21) animals confirm the hypothesis of a developmental switch (Bureau & Mulle, 1998) that could correspond to a displacement of AMPARs from the axonal to the somato‐dendritic compartment. Interestingly, it has been reported that presynaptic ionotropic glutamate receptors promote the maturation of GABAergic basket/stellate interneurones and increase the size of their axonal terminals thus enhancing GABA release (Fiszman et al 2005, 2007). It seems likely that activation of presynaptic Ca 2+ ‐permeable AMPARs represents an important step in the developing cerebellum.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, activation of presynaptic NMDARs promotes the spontaneous release of Ca 2+ from presynaptic ryanodine‐sensitive Ca 2+ stores (RyCSs) thus enhancing the release of GABA at the MLI‐Purkinje cell synapse (Duguid & Smart, 2004) and activation of extrasynaptic NMDARs induces a switch in synaptic receptor subtypes under PKC control (Sun & Liu, 2007). Finally, it has been demonstrated in cerebellar cultures that AMPARs are present in developing GABAergic terminals and their activation affects the size of GABAergic terminals and spontaneous GABA release (Fiszman et al 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…AMPA Receptor Function in Presynaptic Signaling. AMPA receptors are present in the presynaptic compartments of neurons in hippocampus, striatum, and spinal cord (Lu et al, 2002;Schenk et al, 2003;Fujiyama et al, 2004;Fiszman et al, 2007;Haglerod et al, 2017) and can potentially influence synaptic function by multiple means, including as autoreceptors that respond to glutamate in the synaptic cleft or as receptors on nearby terminals to impact vesicular release properties in response to glutamate that has diffused from a different synapse. Whereas the autoreceptor paradigm represents a conventional form of presynaptic regulation, the second form allows AMPA receptors to participate in intersynaptic communication.…”
Section: Roles Of Ampa and Kainate Receptors In Neuronal Functionsmentioning
confidence: 99%
“…Whole-cell recordings confirmed the functional relevance of these morphological changes. Indeed, kainate increased the spontaneous synaptic release from GABAergic interneurons in cerebellar cultures [ 38 ].…”
Section: Physiological Functions Of Presynaptic Amparmentioning
confidence: 99%